Association between serum vitamin C and HPV infection in American women: a cross-sectional study - Chunqin Zheng; Zhixiang Zheng; Weiqiang Chen (BMC, 2022)
Abstract Background Evidence regarding the relationship between serum vitamin C levels and human papillomavirus (HPV) infection is limited. Therefore, this study aimed to investigate whether serum vitamin C levels are independently associated with HPV infection. Methods Data for this cross-sectional study were obtained from the National Health and Nutrition Examination Survey 2003-2006. A total of 2174 women, 18-59 years of age, were enrolled in this study. The associations between serum vitamin C levels (continuous and categorical forms) and cervicovaginal HPV infection were estimated using weighted logistic regression. Results The adjusted binary logistic regression showed that serum vitamin C was not associated with the risk of HPV infection after adjusting for age, race, poverty income ratio, alcohol consumption, smoking, body mass index, education, and health condition (odds ratio [OR] 0.998, 95% confidence interval [CI] 0.994-1.001). Serum vitamin C levels were converted from a continuous variable to a categorical variable for the analysis. Compared with the vitamin C deficiency and hypovitaminosis groups, there was a negative correlation between vitamin C and HPV infection when vitamin C was adequate (OR 0.7, 95% CI: 0.52-0.94); however, when the serum vitamin C level was inadequate and saturated, this negative correlation was weaker or nonexistent (OR 0.76, 95% CI 0.56-1.03 and OR 0.76, 95% CI 0.55-1.04, respectively). A nonlinear relationship was detected between vitamin C level and HPV infection. Furthermore, we performed subgroup analysis of different models and found that serum vitamin C concentration was negatively associated with HPV infection in women ≥ 25 years of age; however, in women < 25 years of age, serum vitamin C levels were not associated with HPV infection. Conclusion The results from this United States nationally representative sample supported the hypothesis that there was a U-shaped relationship between serum vitamin C levels and HPV infection. Future studies are warranted to assess the association between vitamin C and HPV persistence and clarify the underlying mechanisms of these associations.